2013
DOI: 10.1111/1744-7917.12019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plant nutrition on aphid size, prey consumption, and life history characteristics of green lacewing

Abstract: Plant quality can directly and indirectly affect the third trophic level. The predation by all the instars of green lacewing, Chrysoperla carnea (S.) (Neuroptera: Chrysopidae) on the cereal aphids, Rhopalosiphum padi (L.), and Sitobion avenae (F.) at varying nitrogen fertilizer levels was calculated under laboratory conditions. Wheat plants were grown on four nitrogen fertilizer levels and aphids were fed on these plants and subsequently offered as food to the C. carnea. Aphid densities of 10, 30, and 90 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…PDSs may also block the molecular transport in plant cells, which may contribute to the limited development of vegetative and generative organs (Osuagwu et al 2013). Aqueel et al (2014) confirmed that plant quality can affect the feeding of aphids and other consumers with higher trophic level. On high quality plants the aphids produced most offspring and were characterized by a higher population intrinsic growth rate (Stadler et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…PDSs may also block the molecular transport in plant cells, which may contribute to the limited development of vegetative and generative organs (Osuagwu et al 2013). Aqueel et al (2014) confirmed that plant quality can affect the feeding of aphids and other consumers with higher trophic level. On high quality plants the aphids produced most offspring and were characterized by a higher population intrinsic growth rate (Stadler et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it might respond to extra increase in plant biomass after mineral fertilizer supply, potentially explaining why S . avenae responds after fertilization in some studies [ 50 ], but not in others [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…An extended time of larval development may signal that poor nutrition or antibiosis is at work. A longer development time, even if it does not lead to increased mortality, would be beneficial because larvae would be exposed to other mortality factors, especially the activities of biological control agents (i.e., predators and parasitoids), which have been shown to positively modulate their consumption behavior towards nutrition-deficient prey [56]. An extended period of larval development could also reduce the possibility of having two complete successful OBLR generations, thereby impacting larval fitness during the early fall, when they prepare for and enter overwintering diapause (as second or third instars) as well as post-overwintering sur- …”
Section: Developmental Parametersmentioning
confidence: 99%